PELINDUNGAN BAGI KELOMPOK BERISIKO GANGGUAN JIWA - Andina, Elga (Jurnal Aspirasi, 2013)
The increasing number of People With Mental Health Disorder (PWMHD) shows fragile protection to people. Medical Human Resource can hardly handle this condition; therefore we need preventive approach to avoid new PWMHD. This protection should be focus more to those who’s at risk in order to maintain their mental health quality. This study classifies 4 groups risked to mental health disorder: according to age; psychosocial condition; under threat condition, and physical condition. The Indonesia’s People House of Representative needs to make laws based on mental health’s perspective to ensure protection against mental disorder’s risk.